2023
DOI: 10.1007/s11356-023-27133-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of negative air ions on human health and integrated multiomics to identify biomarkers: a literature review

Abstract: Environmental pollution seriously affects human health. The concentration of negative air ions (NAIs), which were discovered at the end of the nineteenth century, is one of the factors used to evaluate air quality. Additionally, NAIs have been widely considered markers by scholars due to their unique biological function. The aim of this study was to summarize existing research and propose future research on the generation and temporal and spatial dynamic patterns of NAIs concentrations as well as the relations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…The XXXV th Annual International Occupational Ergonomics and Safety Conference Munich, Germany October 9-10, 2023 Bittner and Sakuragi (2006) -supported NIA's antioxidant effects, with Iwama (2004) classically demonstrating increased flexibility of stressed erythrocytes (RBCs). Xiao et al (2023) -in their contemporary review and research -have shown that negative-ion air is broadly antioxidative, anti-inflammatory, and antiapoptotic (i.e., supportive of Iwama, 2004 andSakuragi, 2006).…”
Section: Negative Ion Air (Nia)mentioning
confidence: 99%
“…The XXXV th Annual International Occupational Ergonomics and Safety Conference Munich, Germany October 9-10, 2023 Bittner and Sakuragi (2006) -supported NIA's antioxidant effects, with Iwama (2004) classically demonstrating increased flexibility of stressed erythrocytes (RBCs). Xiao et al (2023) -in their contemporary review and research -have shown that negative-ion air is broadly antioxidative, anti-inflammatory, and antiapoptotic (i.e., supportive of Iwama, 2004 andSakuragi, 2006).…”
Section: Negative Ion Air (Nia)mentioning
confidence: 99%